Divergent blood pressure response after high-intensity interval exercise: A signal of delayed recovery? - Hunter, G. R.; Fisher, G.; Bryan, D. R.; Borges, J. H.; Carter, S. J. (The Journal of Strength and Conditioning Research, 2018)
The objective of this commentary is to highlight potential factors influential to the adaptation of high-intensity exercise. Herein, we present a rationale supporting the contention that elevated systolic blood pressure, after a bout of high-intensity exercise, may be indicative of delayed/incomplete recovery. Relative to type I skeletal muscle fibers, the unique cellular/vascular characteristics of type II muscle fibers may necessitate longer recovery periods, especially when exposed to repeated high-intensity efforts (i.e., intervals). In addition to the noted race disparities in cardiometabolic disease risk, including higher mean blood pressures, African Americans may have a larger percentage of type II muscle fibers, thus possibly contributing to noted differences in recovery after high-intensity exercise. Given that optimal recovery is needed to maximize physiological adaptation, high-intensity training programs should be individually-tailored and consistent with recovery profile(s). In most instances, even among those susceptible, the risk to nonfunctional overreaching can be largely mitigated if sufficient recovery is integrated into training paradigms.